Searching for the economic gradient in self-assessed health - Lokshin, Michael (Policy research working paper, 2005)
"Can self-assessed health be relied on to identify the true socioeconomic gradients in health status? The self-assessed health of Russian adults in 2002 shows remarkably little gradient with respect to economic welfare. The authors document this finding and assess its robustness to the assumptions routinely made in measuring health and welfare. They find that the expected economic gradient only emerges once one focuses on the component of self-assessed health that is explicable in terms of age and more objective health indicators and one allows for broader dimensions of economic welfare than captured by standard income-based measures. The results point to the need for caution in analyzing and interpreting self-assessed health data. "--World Bank web site